Transfer of MicroRNA-216a-5p From Exosomes Secreted by Human Urine-Derived Stem Cells Reduces Renal Ischemia/Reperfusion Injury - Zhang, Yinmei; Wang, Junxiong; Yang, Boxin; Qiao, Rui; Li, Aiwei; Guo, Han; Ding, Jie; Li, Hui; Ye, Hong; Wu, Di; Cui, Liyan; Yang, Shuo (Frontiers in Cell and Developmental Biology, 2020)
Human urine-derived stem cells (USCs) protect rats against kidney ischemia/reperfusion (I/R) injury. Here we investigated the role of USCs exosomes in protecting tubular endothelial cells and miRNA transfer in the kidney. Human USCs and exosomes from urine-derived stem cells (USCs-Exos) were isolated and verified by morphology and specific biomarkers. USC-Exos played a protective role in HK-2 cells exposed to H/R. USCs-Exos were rich in miR-216a-5p, which targeted phosphatase and tensin homolog (PTEN) and regulated cell apoptosis through the Akt pathway. In HK-2 cells exposed to H/R, incubation with USC-Exos increased miR-216-5p, decreased PTEN levels and stimulated Akt phosphorylation. Exposure of hypoxic HK-2 cells to exosomes of USCs pretreated with anti-miR-216a-5p can prevent the increase of miR-216-5p and Akt phosphorylation levels, restore PTEN expression and promote apoptosis. The dual-luciferase reported gene assay in HK-2 cells confirmed that miR-216a-5p targeted PTEN. In rats with I/R injury, intravenous infusion of USCs exosomes can effectively induce apoptosis suppression and functional protection, which is associated with decreased PTEN. Infusion of exosomes from anti-miR-216a-5p transfected USCs weakened the protective effect in the I/R model. Therefore, USCs exosomes can reduce renal I/R injury by transferring miR-216a-5p targeting PTEN. Potentially, USCs exosomes rich in miR-216a-5p can serve as a promising therapeutic for AKI.